597 Counting on You to do The Count: An Unusual Case Report of a Delayed and Missed Gossypiboma Secondary to Swiss Cheese Model Failings. (12th October 2021) - Amin, P; Chan, T
Abstract: Introduction: Gossypiboma is a term describing a retained surgical swab which is a serious complication following any surgical intervention. The incidence of these cases is wholly under reported, partly due to medicolegal aspects, but also due to the misnomer of diagnosis. In this case, we discuss the multifactorial deficiencies which led to a significant morbidity in a patient who had remained asymptomatic for nine years since index surgery. Case Presentation: A 40-year-old woman presented to the emergency department febrile with a one week history of abdominal pain, on a background of a one year history of chronic pain. The patient's surgical history demonstrated an ovarian fibroid excision and a subtotal hysterectomy nine and six years ago, respectively. It was later noted the chronic abdominal pain had been previously investigated with positive findings on imaging and biopsy, however, she was lost to follow up. A year later, she presented with an acute abdomen and operative findings of a large abscess cavity, containing a retained swab, with small bowel fistulation were noted. Conclusions: This reiterates the importance of surgical safety checklists, and often despite this there are many factors that can eventually lead to complete alignment of the holes in the Swiss Cheese leading to unfavourable outcomes. It is imperative to remain hypervigilant during checkpoints, particularly in emergencies where the unpredictability of the operation leads to human error. Gossypiboma remains a serious cause for morbidity and mortality, thus the potential for modified safety checklists or alternative methods for surgical counts.